The Pirdot Leaves Extract (Saurauia vulcani Korth) As Natural Antioxidant to Inhibit Oxidation Reaction of Crude Palm Oil (CPO): Ekstrak Daun Pirdot (Saurauia vulcani Korth) sebagai Antioksidan Alami untuk Menghambat Reaksi Oksidasi pada Crude Palm Oil (CPO) - Musa, Weny J A; Harianja, Lokky Sardomu; Sriwijayanti, Sriwijayanti; Yulianti, Nani; Situmeang, Boima (Stannum : Jurnal Sains dan Terapan Kimia, 2024)
The Pirdot plant (Saurauia vulcani Korth) is a wild plant that grows abundantly in tropical regions such as in North Sumatra. The active compounds found in Pirdot plant leaves are known to have good antioxidant activity. The aim of this research is to evaluate the n-hexane and methanol extracts of Pirdot plant leaves in inhibiting oxidation in crude palm oil (CPO). In this study, the Pirdot plant leaves were extracted using n-hexane (EHP) and methanol (EMP) solvents. The effectiveness of adding both extracts to the quality of CPO was tested for eight days using the parameters of free fatty acid content and peroxide value. The results of the effectiveness test for adding both extracts to CPO showed a good inhibitory effect on the oxidation reaction in CPO. The EMP extract at a concentration of 5000 ppm was more effective in maintaining the quality of CPO for 8 days, with a free fatty acid content of 3.09% and a peroxide value of 14.03 meq O2/kg.